2012
DOI: 10.15835/nbha4027993
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar Selection and Pest Control Techniques on Organic White Cabbage Yield

Abstract: In Romania, as in many other countries, white cabbage is one of the most important vegetable crop species. The experiment was performed in the NE of the country during 2008-2009 in order to measure the impact of cultivar choice and pest control techniques on organic white cabbage [Brassica oleracea (L.) var. capitata f. alba (D.C.)]. This experiment included early, summer and autumn crops. The early crop compared four cultivars, the summer crop two cultivars, and the autumn crop three cultivars. The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…For example, the use of exclusion nets in an organic apple orchard kept the damage caused by codling moths below 0.1% (Sauphanor et al 2012). Likewise, covering organic white cabbages with an agrotextile in combination with common organic pest control techniques also resulted in higher yield (Stoleru et al 2012). Sticky-tape barriers may reduce the pest population (Drummond et al 2012) but are not selective to injurious insects.…”
Section: Biological Control Of Pestsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the use of exclusion nets in an organic apple orchard kept the damage caused by codling moths below 0.1% (Sauphanor et al 2012). Likewise, covering organic white cabbages with an agrotextile in combination with common organic pest control techniques also resulted in higher yield (Stoleru et al 2012). Sticky-tape barriers may reduce the pest population (Drummond et al 2012) but are not selective to injurious insects.…”
Section: Biological Control Of Pestsmentioning
confidence: 99%
“…The development and testing of biopesticides and lures also contributed to pest management control for organic fruit and vegetable crops (Rajapakse and Ratnasekera 2007;Michereff-Filho et al 2008;Aselage and Johnson 2009;Efrom et al 2011;Wearing et al 2011;Arroyo et al 2012;Bisotto-de-Oliveira et al 2012;Stoleru et al 2012;Attia et al 2013). For organic Japanese plum, sulfur was shown to be effective against powdery mildew, red spider, and plum gall nut; potassium soap and natural pyrethrins maintained aphid populations at moderate levels; and entomopathogenic nematodes controlled flatheaded rootborer (Arroyo et al 2012).…”
Section: Biological Control Of Pestsmentioning
confidence: 99%
“…Recent research on the outside cabbage crop in the temperate climate highlighted, Timpurie de Vidra cultivar (cv) of early cabbage is most resistant to the cabbage fly (8.5% degree of attack) in comparison with the Golden acre cv., where the degree of attack was 14.2%, during two study years [21].…”
Section: Selection Of Cultivars According To the Resistance And Ecolomentioning
confidence: 99%
“…Permeability tests. The water penetration test was carried out by placing the samples in a water bath beaker at room temperature (~22 °C) for 30 seconds and then the rate of absorption or permeability was calculated as a ratio of the weight of the soaked pellet with respect to the original weight [BAKARI and NGADI, 2013, BONEA et al, 2017, PENTEA et al, 2016, STOLERU et al, 2012 .…”
Section: Density Testsmentioning
confidence: 99%
“…The strong peak around 1650 cm -1 indicated the C=O stretching of a carbonyl group in the sub-Saharan rice husks [BAGIU et al, 2012;BUTNARIU and CORADINI, 2012] . The strong peak at around 1025 cm -1 indicated the strong presence alcohols [BUTNARIU et al, 2012, STOLERU et al, 2012 , carboxylic acids, ethers and esters [LAMBERT et al, 2011] . Also, the secondary peak around 1100-1217 cm -1 indicated silica presence in the form of cellulose-silicates [NDAZI et al, 2007] which the proximate analysis ash content confirmed.…”
Section: Figure 1 Particle Size Distribution Of Rice Huskmentioning
confidence: 99%